2022
DOI: 10.3389/fneur.2022.993559
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of carotid artery free-floating thrombus—A single center, consecutive cohort analysis

Abstract: IntroductionCarotid free-floating thrombus (CFFT) is a rare cause of stroke and is thought to be associated with a high risk of recurrent cerebrovascular ischaemic events. The existing data on the natural history and optimal treatment modalities of CFFT is scanty and no clear recommendations exist.ObjectiveA retrospective analysis, single-center cohort of consecutive patients diagnosed with CFFT was conducted, investigating the risk for recurrent cerebrovascular ischaemic events.MethodsWe performed a single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6,7,10,13,14,[16][17][18]25,26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 With its minimally invasive nature and advanced modern catheters and devices, endovascular thrombectomy, as opposed to CEA, has become the preferred choice for the procedural management of CFFTs at many centers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is insufficient data/evidence to compare the different procedural modalities in managing CFFTs. 6 7 10 13 14 16 17 18 25 26 A retrospective study of 525 cases with CFFTs found no significant difference in outcomes of patients receiving antiplatelet and anticoagulant therapy versus procedural management with endovascular or surgical carotid endarterectomy (CEA). 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations